The non-for-profit banks in Portugal: specificities, social role and evolution - Barradas, R.; Lagoa, S.; Leão, E. (Revista de Economia Solidária, 2011)
This paper establishes the main differences between standard commercial banks and the two non-for-profit banks operating in Portugal (Caixa Agrícola – CA – and Caixa Económica Montepio Geral – CE-MG). In particular, we find differences in the way funds are raised, governance criteria, tax regime, application of profits and attitude towards profit. However, CA is more similar to a typical co-operative/mutual bank than CE-MG. Both banks have modernized and transformed into modern financial groups offering a wide variety of financial products similar to any commercial bank. However, this was not enough to avoid an erosion of their market position in terms of credit and deposits. The 2008 financial crisis’ impact on the profitability of CA was similar to the impact on the industry average, whereas on CE-MG the impact was milder.